2013
DOI: 10.1371/journal.ppat.1003314
|View full text |Cite
|
Sign up to set email alerts
|

The EBV Latent Antigen 3C Inhibits Apoptosis through Targeted Regulation of Interferon Regulatory Factors 4 and 8

Abstract: Epstein-Barr virus (EBV) is linked to a broad spectrum of B-cell malignancies. EBV nuclear antigen 3C (EBNA3C) is an encoded latent antigen required for growth transformation of primary human B-lymphocytes. Interferon regulatory factor 4 (IRF4) and 8 (IRF8) are transcription factors of the IRF family that regulate diverse functions in B cell development. IRF4 is an oncoprotein with anti-apoptotic properties and IRF8 functions as a regulator of apoptosis and tumor suppressor in many hematopoietic malignancies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 80 publications
10
111
0
Order By: Relevance
“…The EBV-encoded protein EBNA3C, which inhibits expression of the cell cycle inhibitor p16 (49), may also promote proliferation of the LMP1-KO EBVinfected cells. Notably, EBNA3C was also recently shown to stabilize the IRF4 protein in EBV-infected B cells (32), and we found that the LMP1-KO EBV-induced lymphomas expressed a high level of IRF4. IRF4 is not only an essential growth and survival factor for activated human DLBCLs (34), but is also required for survival of EBV-transformed LCLs in vitro (32,33).…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…The EBV-encoded protein EBNA3C, which inhibits expression of the cell cycle inhibitor p16 (49), may also promote proliferation of the LMP1-KO EBVinfected cells. Notably, EBNA3C was also recently shown to stabilize the IRF4 protein in EBV-infected B cells (32), and we found that the LMP1-KO EBV-induced lymphomas expressed a high level of IRF4. IRF4 is not only an essential growth and survival factor for activated human DLBCLs (34), but is also required for survival of EBV-transformed LCLs in vitro (32,33).…”
Section: Methodssupporting
confidence: 61%
“…Notably, EBNA3C was also recently shown to stabilize the IRF4 protein in EBV-infected B cells (32), and we found that the LMP1-KO EBV-induced lymphomas expressed a high level of IRF4. IRF4 is not only an essential growth and survival factor for activated human DLBCLs (34), but is also required for survival of EBV-transformed LCLs in vitro (32,33). T cell-derived CD40 signaling may also help to induce IRF4 expression in LMP1-KO EBVinduced lymphomas (35).…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, EBNA3A-and EBNA3B-bound sites are also enriched for IRF4 binding ( (51). However, some lines of evidence suggested that the IRF4 interaction might be more important for EBNA3C, including the increased EBNA3C binding signals at IRF4 sites compared to non-IRF4 sites and the ability of EBNA3C to bind directly to IRF4 and promote its stabilization (35,55). When we restricted our analysis to sites uniquely bound by EBNA3A, EBNA3B, or EBNA3C, we observed enrichment for the IRF4 binding motif only in the EBNA3C subset.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, the IRF4 DNA motif is highly enriched at promoter sites occupied only by LMP1/noncanonical pathway-activated p52. EBNA3C and LMP1 upregulate IRF4 expression (17,47), which may then tether p52 to these sites. Similarly, an E-box motif is enriched at LCL promoters bound predominantly by LMP1/canonical pathway-activated cRel, suggesting that an E-box-bound host transcription factor such as c-Myc may tether cRel homodimers to these sites.…”
Section: Lymphoblastoid B-cell Nf-b Genomic Binding Landscapementioning
confidence: 99%